Prospects for the Development of the National Social Insurance System - Hamraeva, F. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article covers the areas of development of the social insurance sector in Uzbekistan through digitalization, the prospects for using the experience of foreign countries in the introduction of digital technologies in the field.